Assessment of Quality of Life, Tumour Control and Adverse Effects Observed in Patients Treated with Palliative Radiotherapy for Unresectable Gallbladder Cancer: A Prospective Interventional Study - Utkarsha Singh; Aradhana Singh; Arun Kumar Yadav; Tabassum Samani; Hari Singh; Anuj Kumar (Journal of Clinical and Diagnostic Research)
Introduction: Treating advanced Gallbladder Cancer (GBC) poses a substantial therapeutic challenge. Palliative chemotherapy is the primary treatment for patients with unresectable tumours. The effectiveness of this treatment in extending lifespan is limited, usually quantified in a few months, and its accompanying harmful effects can significantly impair overall well-being. As a viable alternative, palliative radiation offers the benefits of shorter treatment duration and a potentially lower risk of harmful side-effects. Its potential in the treatment of advanced GBC has not been fully explored, and the existing medical literature on this topic is scarce. However, the promising aspects of palliative Radiotherapy (RT) suggest a hopeful future for its application in treating unresectable GBC.